How Detergents Dissolve Polymeric Micelles: Kinetic Pathways of Hybrid Micelle Formation in SDS and Block Copolymer Mixtures - Myhre, Synne (Langmuir, 2020)
[Image: see text] Mixtures of amphiphilic polymers and surfactants are used in a wide range of applications, e.g., pharmaceuticals, detergents, cosmetics, and drug delivery systems. Still, many questions remain on how the structure and, in particular, the kinetics of block copolymer micelles are affected in the presence of surfactants and what controls the solubilization kinetics. In this work, we have studied the stability and solubilization kinetics of block copolymer micelles upon the addition of the surfactant sodium dodecyl sulfate (SDS) using small-angle X-ray/neutron scattering. The ability of the surfactant to dissolve polymer micelles or form mixed micelles has been investigated using two types of amphiphilic polymers, poly(ethylene-alt-propylene)–poly(ethylene oxide) (PEP1-PEO20) and n-alkyl-functionalized PEO (C(28)-PEO5). The exchange kinetics of C(28)-PEO5 micelles are in the order of hours, while PEP1-PEO20 micelles are known to be frozen on a practical timescale. In this work, we show that the addition of SDS to PEP1-PEO20 provides virtually no solubilization, even after an extended period of time. However, upon adding SDS to C(28)-PEO5 micelles, we observe micellar dissolution and formation of mixed micelles occurring on the timescale of hours. Using a coexistence model of mixed and neat micelles, the SAXS data were analyzed to provide detailed structural parameters over time. First, we observe a fast fragmentation/fission step followed by a slow reorganization process. The latter process is essentially independent of concentration at low volume fraction but is greatly accelerated at larger concentrations. This might indicate a crossover from a predominance of molecular exchange to fusion/fission processes.